Hubungan Gaya Kepemimpinan dan Lingkungan Kerja Dengan Motivasi Kerja Anggota Satuan Brigade Mobile Kepolisian Daerah Sumatera Utara - Siti Mayasari Hasibuan; M. Rajab Lubis; Suryani Hardjo (Universitas Medan Area, 2019)
This study aims to determine the relationship between leadership style and work environment with work motivation. The research was conducted at BRIMOB POLDA SUMUT. The number of respondents in this study was 106 members of BRIMOB POLDA SUMUT with sampling technique random sampling. Based on spearman rank data analysis, there is a significant level between leadership style (X1) with work motivation (Y) with significant value 0.000 0,05, that was to prove that there was a partial relationship of leadership style with work motivation. While the working environment relation (X2) with work motivation (Y) with significant value 0,000 0,05. It proves that there was a partial relationship work environment with work motivation. While the significance level of leadership style (X1) and work environment (X2) with work motivation (Y) with significant value 0,000 0,05 were related simultaneously, the hypothesis in this research was accepted. The correlation of leadership style relation and work environment with work motivation of BRIMOB members was 49.7% .